Crimes, Punishments and Procedural Privileges of Clergy in Juan Bernal Díaz De Luco’s Practica Criminalis Canonica (Italian Review of Legal History, 2024)
The essay provides a legal analysis of the theories upheld by Bishop Juan Bernal Díaz de Luco in his most famous work, the pioneering Practica canonica criminalis, published in 1543. After a biographical reconstruction of the author’s personality, in the historical context of the Counter-Reformation in which he was one of the most accredited protagonists, an initial investigation is made into the structure of the Practica, its sources and the method of the Sevillian jurist. Some of the topics dealt with in his work are then explored, particularly focusing on the debate about the punishments to be imposed for certain crimes and some procedural problems: the torture of clergy, the interrogation of the offender with a de veritate oath, and the admissibility of lay witnesses versus clerics. From this analysis it emerges that Dr. Bernal, as Díaz de Luco was also called, is distinguished both by his tendency to defend and preserve the procedual privileges of clergy, and by the severity and rigour with which, in the midst of Erasmian reformism, he shapes the Church’s punitive response to the crimes of clergy. From this point of view, Díaz de Luco can be considered a skillful defender of the rights, but also a strenuous reformer of the customs of clergy.
Keywords: Juan Bernal Díaz de Luco; History of Criminal Law; Teaching 13th c.; Theology; Canon Law; Roman Law; Paris; Crimes of Clergy; Torture